2017
DOI: 10.3892/mmr.2017.7103
|View full text |Cite|
|
Sign up to set email alerts
|

Upregulation of microRNA-25-3p inhibits proliferation, migration and invasion of osteosarcoma cells in vitro by directly targeting SOX4

Abstract: Osteosarcoma (OS) is among the most common primary tumors of bone tissue, and occurs primarily in children and young adults. Despite the development of novel therapeutic approaches, the prognosis of OS remains poor. MicroRNAs (miRNAs) are involved in the development and progression of various types of human cancer and may have potential as novel therapeutic targets for cancer treatment. The present study aimed to investigate the expression and biological functions of miRNA‑25‑3p in OS, and explore the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“… 16 26 27 For example, SOX4, as a target of microRNA-212 and microRNA-25-3p together with miR-132, could weaken these miRNAs-mediated inhibition effects on progression of OS cells. 16 18 19 Consequently, we further demonstrated that SOX4 was a target gene of miR-132-3p by bioinformatics analysis, luciferase reporter assays, and western blot assays, the results of which were consistent with those in a previous study. 16 Additionally, miR-132-3p repressed proliferation and induced apoptosis of OS cells, while this effect of miR-132-3p was partly abrogated by SOX4 overexpression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 16 26 27 For example, SOX4, as a target of microRNA-212 and microRNA-25-3p together with miR-132, could weaken these miRNAs-mediated inhibition effects on progression of OS cells. 16 18 19 Consequently, we further demonstrated that SOX4 was a target gene of miR-132-3p by bioinformatics analysis, luciferase reporter assays, and western blot assays, the results of which were consistent with those in a previous study. 16 Additionally, miR-132-3p repressed proliferation and induced apoptosis of OS cells, while this effect of miR-132-3p was partly abrogated by SOX4 overexpression.…”
Section: Discussionsupporting
confidence: 91%
“…Among candidate genes, SOX4 has been identified as an oncogene in OS ( Fig. 3A ), 16 18 19 and was chosen for further study. To validate whether the putative binding sites of SOX4-3'UTR and miR-132-3p are important for the interaction between miR-132-3p and SOX4, dual luciferase reporter assays and mutation assays were performed.…”
Section: Resultsmentioning
confidence: 99%
“…We predicted the target gene of miR-188 by using the TargetScan and PicTar algorithm software and found that SOX4 is a potential target of miR-188. SOX4 is a key oncogene in OS development (20,21). Therefore, we chose SOX4 for further investigation.…”
Section: Mir-188 Overexpression Inhibited Os Cell Migration and Invasmentioning
confidence: 99%
“…An abnormal SOX4 overexpression is often linked to tumorigenicity and cancer stemness (30). SOX4 is upregulated in various cancers, such as ovarian cancer (29), renal cell carcinoma (31), lung adenocarcinoma (32), gastric carcinoma (33), and OS (34). Previous studies showed that SOX4 is regulated by miRNAs in OS and involved in the promotion of OS progression.…”
Section: Mir-188 ------------------------------------mentioning
confidence: 99%
“…Previous studies have demonstrated that miR-25 promotes cancer cell proliferation, migration and invasion by regulating the expression of various protein in tumor-associated signaling pathways [10][11][12][13]. However, another study demonstrated that miR-25 suppresses cell growth and mobility of osteosarcoma via targeting SOX4 [14]. In addition, other studies have shown that miR-25 inhibits cell apoptosis in various cancers, including gastric adenocarcinoma, lung cancer and pancreatic cancer [15][16][17][18].…”
mentioning
confidence: 99%